EFFICACY OF SOME PLANT EXTRACTS ON POSTHAVEST FUNGAL ROT PATHOGENS OF SWEET POTATO (Ipomoea batatas L.) IN SELECTED LOCAL GOVERMENT AREAS OF BORNO STATE - I. Y, MSHELIA; I.B, CHIMBEKUJWO; B.G, ZAKARI; S.H , PUMA (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Sweet Potato (Ipomoea batatas) is attacked by fungal diseases especially fusarium, soft and dry rot. Efficacy of the plant extracts were carried out in the laboratory of Plant Science Moddibbo Adama University Yola in a Completely Randomized Design. Rot incidence was of universal in all the four locations Biu, Bayo, Hawul and Kwata kusar with an average of 9.06%. Biu had the highest incidence of 13.75%, Hawul with 8.75%, Kwaya-kusar had 7.5%, with the least as observed at Bayo 6.25%.and three organisms were responsible for the rots: (Aspergillus niger, Aspergillus flavus and Rhizopus stolonifer. Aspergillus niger had the highest level of occurrence with the average of 5 pathogens per sample location, Rhizopus stolonifer 4 while Aspergillus flavus had the least 3 organisms per. Aqueous extracts of Balanite aegyptica and Parkia biglobosa pulp, leaf, stem and root bark at 60% proved to be effective in controlling mycelial growth in all the three organisms. Balanite aegyptica leaf controlled mycelial growth of Aspergillus flavus Aspergillus niger, and Rhizopus stolonifer. Aqueous to 5.74, 6.74 and 7.54 mm invitro respectively and Aspergillus flavus 6.07 invivo. Balanite aegyptica pulp reduced mycelial growth of Aspergyllus niger and Rhizopus stolonifer invivo 6.26 and 6.25mm.